Life Insurance and Working Women: A Critical Study of Factors Affecting the Purchase Decision - Srivastava, Manish; Rastogi, Megha (Indian Journal of Marketing, 2010)
As the economy is developing, the mind set of the people is also changing at a very fast pace. Some decades back, the best place for women was considered to be their home. It was thought that women are born to look after the family and children. They were not allowed to work outside because it ruined the reputation of the family and at the same time, it was not accepted by society. But now, the scene has changed and so has the position of women in society. Women are working in every field. Their earning is at par with that of their male counterparts and they enjoy both personal and professional life, but in terms of insurance, they are either under insured or uninsured. Despite all of the changes, many married women still rely on their husbands’ insurance policy to protect them. Studies have shown that while women indicate they understand life insurance as a product, few have quantified its economic value.